2020
DOI: 10.1002/celc.202001312
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐Doped CuCo2O4 Oxide with Partial Amorphous Phase as a Robust Electrocatalyst for the Oxygen Evolution Reaction

Abstract: It is highly desirable to develop efficient and low‐cost electrocatalysts for the oxygen evolution reaction (OER) to improve the efficiency of water electrolysis. Here, we report a strategy doping with a small amount of phosphorus to make inactive and low‐cost spinel CuCo2O4 (CCO) turn into high‐efficiency and superior to the noble metal catalyst RuO2. The spinel CuCo2O4−P0.5 (CCP0.5) shows the best OER performance with a small overpotential of 290 mV at a current density of 10 mA cm−2 and a low Tafel slope of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…However, doping with other atoms can improve the intrinsic activity and the conductivity of CuCo 2 O 4 . [ 48,139 ] Other strategies that have been explored to improve the OER performance of CuCo 2 O 4 are discussed below.…”
Section: Bimetallic‐based Spinels For Oer and Their Improvementsmentioning
confidence: 99%
“…However, doping with other atoms can improve the intrinsic activity and the conductivity of CuCo 2 O 4 . [ 48,139 ] Other strategies that have been explored to improve the OER performance of CuCo 2 O 4 are discussed below.…”
Section: Bimetallic‐based Spinels For Oer and Their Improvementsmentioning
confidence: 99%
“…In particular, the spinel AB 2 O 4 (A and B representing transition metals) containing 3d transition metals have exhibited great potential of OER performance. , Among these spinel AB 2 O 4 , CuCo 2 O 4 has been greatly applied in supercapacitors, , electrochemical sensors, , and electrocatalysts, , due to its unique spinel structure. Unfortunately, its low electric conductivity and limitation exposure of catalytic sites seriously hinder its further improvement of OER performance . As is well known, the partial tetrahedral and octahedral interstices are occupied by the Co cations in the CuCo 2 O 4 crystal lattice, and the remaining unfilled interstices provide a chance to accommodate the migration of cations.…”
Section: Introductionmentioning
confidence: 99%
“…etc.) is a valued strategy to regulate the electronic structures and increase active sites, thus significantly boosting the electrocatalytic activity of OER. , For example, Huo et al reported the fabrication of Co 3 O 4 nanosheets with enriching oxygen vacancies by an Ar plasma engraving approach, in which the introduction of oxygen vacancies significantly improves the conductivity and accelerates the formation of extensive active sites, thus resulting in the great enhancement of OER performance . Qiu and co-workers developed a p–n heterojunction interface method to fabricate CeO 2 /Co 3 O 4 compound with abundant Co 2+ octahedral sites, which significantly enhanced its OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…[5] But the OER is more kinetically sluggish because OER is a four-electron transfer reaction, while the HER needs only two electrons. [6] Therefore, in order to use the method of water electrolysis and efficiently convert other renewable energy into hydrogen energy, a good electrocatalyst for OER is indispensable, which can drive larger current density at low overpotential values. [7] At present, the most widely used OER catalysts are RuO 2 and IrO 2 , However, it is difficult to achieve their large-scale application because of their high costs and scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…Water electrolysis consists of hydrogen evolution reaction (HER) and OER [5] . But the OER is more kinetically sluggish because OER is a four‐electron transfer reaction, while the HER needs only two electrons [6] . Therefore, in order to use the method of water electrolysis and efficiently convert other renewable energy into hydrogen energy, a good electrocatalyst for OER is indispensable, which can drive larger current density at low overpotential values [7] .…”
Section: Introductionmentioning
confidence: 99%